Investigation of immobilized filamentous fungi for treatment of real textile industry wastewater using up flow packed bed bioreactor. (September 2019) - Arikan, Ezgi Bezirhan; Isik, Zelal; Bouras, Hadj Daoud; Dizge, Nadir
Abstract: In this study, two filamentous fungi Aspergillus carbonarius M333 and Penicillium glabrum Pg1 were immobilized in macro porous polymeric support (MPPS) to treat real textile industry wastewater. The color and chemical oxygen demand (COD) removal efficiencies were tested in a batch and continuously operated up flow packed bed bioreactor. The protein concentration was also measured for different pH and MPPS amount. Wastewater inlet pH was tested between 4.5 and 6.0 and pH 5.5 was chosen optimum working pH in order to enhance the highest color and COD removal efficiencies. Moreover, MPPS amount was also tested from 1 to 9 pieces and the highest color and COD removal efficiencies were obtained with 9 pieces. The results showed that 98.2% decolorization and 69.8% COD removal efficiencies were obtained by batch experiments. However, 78.8% decolorization and 67.7% COD removal efficiencies were achieved by up flow packed bed bioreactor. The color and COD removal efficiencies were measured 78.8%, 72.1%, 70.2% and 67.7%, 62.5%, 60.0%, respectively, when the up flow packed bed reactor was operated repeatedly for 3 cycles. The immobilized fungi on MPPS were characterized by Scanning Electron Microscopy (SEM). Highlights: AC and PG fungi were immobilized in macro porous sponge. Batch and continuous experiments were examined for treatment of textile wastewater. 98.2% decolorization and 69.8% COD removal was obtained by batch experiments. 78.8% decolorization and 67.7% COD removal was obtained by packed bed bioreactor.